Analisis Penanganan Masalah Anak Panti di Panti Asuhan Tunas Kasih Olayama Raya - Tania Octa Violla; Septira Razin Fadhilah; Rachel Yohana Vatreciya Purba; Fariz Ahmad Ghani Harahap; Fajar Utama Ritonga (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
The nuclear family is a family consisting of father, mother and children. The family is a place for children to interact in learning values through family behavior patterns and connecting children with the environment outside the home. Children are a gift from God that must be looked after, cared for, and fulfilled their needs as they should. However, not all children feel the same way that they should. For this reason, the orphanage exists as a place to accommodate children who do not feel that way. An orphanage or child social welfare institution (LKSA) according to the Indonesian Ministry of Social Affairs, is a child social welfare business institution that has the responsibility to provide social welfare services to neglected children by carrying out sponsorship and alleviation of abandoned children. Children may be considered as someone who easily forgets what they feel. However, children can also be figures who remember something that happened to them and cause resentment to arise. Therefore the handling of problems carried out against children must be carried out as they should.